Pengaruh Penggunaan Aplikasi EMIS Dalam Menunjang Pengolahan Data - Nurhidayah (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
This research aims to investigate the use of the Education Management Information System (EMIS) application in Madrasah Tsanawiyah (MTs) in West Pasaman District. The study adopts the Technology Acceptance Model (TAM) approach to understand the factors influencing technology adoption by individuals. The constructs used in this study are perceived ease of use, perceived usefulness, attitude towards use, and actual system use. The sample for this research consists of 32 operators from MTs in West Pasaman District. The results show a correlation between system quality and data processing, as well as a correlation between usage effectiveness and data processing. Thus, the use of the EMIS application in MTs West Pasaman can provide benefits in improving administrative efficiency, data processing, and decision-making. This research provides valuable insights for educational organizations in adopting information technology to enhance their efficiency and effectiveness.